Entomological Collections and Identifications of Mosquito Faunas in Selected Area Councils of Nigeria Federal Capital Territory (Lafia Journal of Scientific and Industrial Research, 2024)
Mosquito survey and identification are foundational elements of an effective vector management plan. The present study therefore aimed to collect and identify various mosquito species in some selected Area Councils in the Federal Capital Territory (FCT), Nigeria. Larval of various species of mosquitoes were collected and identified in difference breeding sites across selected Area councils in the FCT. The collected larvae were raised to adult stage and were further identified using morphological key. Data obtained were analysed using SPSS version 27.0 and p-value was set at 95%.  Samples were collected from Abuja Municipal, Gwagwalada and Bwari area councils. The study identified Anopheles funestus, 150(9.8%), as the least mosquito species collected and Culex quinquefasciatus, 307 (20.1) was the most abundance species in the study areas. Mosquito species co-exist in various breeding sites with Anopheles species mostly associated with temporary breeding. The study provides a baseline data concerning mosquito vector population and composition in the FCT. This information thus informs the public and vector management officials about the risks and the need to scale-up preventive measures against human-vector contact.
Keywords: Mosquito species; FCT; Public health; Breeding sites